2012
DOI: 10.22146/ijc.21339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycerol Separation on Palm Oil Transesterification

Abstract: 04-7182-2006.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…This calorific value is one of the most important parameters of biodiesel that provides the heat of combustion. The biodiesel quality from this parameter can also determine the qualifications in diesel fuel application [26]. In this study, calorific value of the biodiesel was found to be 7141.75 cal/g.…”
Section: Functional Materialsmentioning
confidence: 59%
“…This calorific value is one of the most important parameters of biodiesel that provides the heat of combustion. The biodiesel quality from this parameter can also determine the qualifications in diesel fuel application [26]. In this study, calorific value of the biodiesel was found to be 7141.75 cal/g.…”
Section: Functional Materialsmentioning
confidence: 59%
“…Minyak atau lemak yang berasal dari tumbuhan dan lemak hewan, serta produk turunannya mempunyai kemungkinan manfaat sebagai bahan baku energi terbarukan seperti pengganti bahan bakar diesel (Srivastava dan Prasad, 2000). Pada generasi sebelumnya, pencarian energi alternatif dilakukan dengan berbagai macam bahan baku diantaranya campuran VGO- (Bezergianni, ., 2009), (Kikhtyanin, ., 2009), (Rahmat, ., 2012) (Sibarani, ., 2007), (Yuswono, ., 2008) dan minyak jelantah (Padmaningsih, ., 2006) dan (Bezergianni, ., 2009). Bahan baku tersebut berasal dari minyak nabati yang banyak digunakan untuk manfaat lain, sehingga memberi dampak negatif dan berkompetisi bagi kebutuhan pangan.…”
Section: Abstrakunclassified
“…The relationship between the processing time (X-axis) and an increase in glycerol volume (Y-axis) follows the inverse model described elsewhere [9]. The curve shape is a nonlinear regression model or a reciprocal model, described as follows:…”
Section: Measurement Of Reactor Performancementioning
confidence: 99%
“…Rahmat et al [9] reported that separation of glycerol could compensate a decrease on methanol and process. The separation of glycerol was conducted as it would be separated easily based on the density.…”
Section: Measurement Of Reactor Performancementioning
confidence: 99%